Novel Approach to Cell Surface Discrimination Between KIR2DL1 Subtypes and KIR2DS1 Identifies Hierarchies in NK Repertoire, Education, and Tolerance - Le Luduec, Jean-Benoît; Boudreau, Jeanette E.; Freiberg, Julian C.; Hsu, Katharine C. (Frontiers in Immunology, 2019)
Cumulative activating and inhibitory receptor signaling controls the functional output of individual natural killer (NK) cells. Investigation of how competing signals impact response, however, has been hampered by the lack of available antibodies capable of distinguishing inhibitory and activating receptors with highly homologous ectodomains. Utilizing a novel combination of monoclonal antibodies with specificity for discrete inhibitory KIR2DL1 and activating KIR2DS1 allotypes found among 230 healthy donors, we investigated allele-specific receptor expression and function driven by KIR2DL1 and KIR2DS1 alleles. We found that co-expression of the HLA-C2 ligand diminishes KIR2DL1, but not KIR2DS1, cell surface staining, but does not impact the respective frequencies of KIR2DL1- and KIR2DS1-expressing cells within the NK repertoire. We can distinguish by flow cytometry NK cell populations expressing the most common KIR2DL1-C245 allotypes from those expressing the most common KIR2DL1-R245 allotypes, and we show that the differential binding informative anti-KIR2DL1/S1 clone 1127B is determined by amino acid residue T154. Although both KIR2DL1-C245 and KIR2DL1-R245 subtypes can be co-expressed in the same cell, NK cells preferentially express one or the other. Cells expressing KIR2DL1-C245 exhibited a lower KIR2DL1 cell surface density and lower missing-self reactivity in comparison to cells expressing KIR2DL1-R245. We found no difference, however, in sensitivity to inhibition or cell surface stability between the two KIR2DL1 isoforms, and both demonstrated similar expansion among NKG2C+ KIR2DL1+ NK cells in HCMV-seropositive healthy individuals. In addition to cell surface density of KIR2DL1, copy number of cognate HLA-C2 hierarchically impacted the effector capacity of both KIR2DL1+ cells and the tolerization of KIR2DS1+ NK cells. HLA-C2 tolerization of KIR2DS1+ NK cells could be overridden, however, by education via co-expressed self-specific inhibitory receptors, such as the heterodimer CD94/NKG2A. Our results demonstrate that effector function of NK cells expressing KIR2DL1 or KIR2DS1 is highly influenced by genetic variability and is calibrated by co-expression of additional NK receptors and cognate HLA-C2 ligands. These findings define the molecular conditions under which NK cells are activated or inhibited, potentially informing selection of donors for adoptive NK therapies.